Developing and evaluating educational programs for students with autism - Magyar, Caroline I.; SpringerLink (Online service). (New York Springer, 2011)
Recent years have witnessed a marked increase both in the number of children diagnosed with autism spectrum disorders (ASDs) and those placed alongside their typically developing peers in general education classrooms. These events bring with them a plethora of challenges, particularly in the areas of program design and educational practices. Developing and Evaluating Educational Programs for Students with Autism offers systematic, evidence-based guidelines,as well as tools, checklists, and other resources?for creating effective learning environments for students across the autism spectrum and the grade span. Planning, development, implementation, and continuous evaluation are examined in detail in this practical volume, which features: An overview of the ASDs, with an emphasis on effective educational practice. In-depth discussion of the ASD Program Development and Evaluation Protocol. A staff training model for personnel working with students with ASD. A detailed framework for student support teams and family-school collaboration. Specific guidelines for conducting needs assessments and student evaluations. Case examples of applications of the protocol on the program, school, and regional levels. Developing and Evaluating Educational Programs for Students with Autism is a uniquely rigorous and thorough reference benefiting school psychologists and special education professionals as well as those in allied educational and mental health fields, including clinical child, school, and developmental psychologists, psychiatrists, and other professionals working with children with autism.
Dedication -- Preface -- Introduction -- Acknowledgements -- Section One: Overview of Autism Spectrum Disorders, Intervention Research, and Considerations in Developing an ASD Program -- Autism Spectrum Disorders in Children and Youth -- Educational Programming for Students with Autism Spectrum Disorders: A Review of the Literature and A Program Development Protocol -- Program Evaluation in Special Education: A Framework for the ASD Program Evaluation Protocol -- Section Two: The ASD Program Development and Evaluation Protocol: Developing and Maintaining the ASD Program Model -- Conducting the Needs Assessment -- ASD Program Development Action Planning -- ASD Staff Training Model -- ASD Classroom Development System: Designing an ASD Classroom -- Student Evaluation -- ASD Student Support Teams: Collaborative Teaming and Problem-Solving -- The ASD Family-School Collaborative Model -- The ASD Program Evaluation Protocol for Continuous Program Improvement -- Section Three: Applications of the ASD Program Development and Evaluation Protocol: A Selection of Case Examples -- Case Example: Inclusion Program Development -- Case Example: Redesigning a Specialized School -- Building Regional Capacity: Select Case Examples.Education and mental health professionals will welcome the information and resources in this book, which will enhance the way they approach the daunting task of developing and evaluating systems-level educational programs for students with ASDs.
Electronic reproduction.
Keywords: Autistic children -- Education; Special education -- Evaluation; Electronic books